Implementasi Pengobatan Gratis Akupunktur sebagai Bentuk Pengabdian Masyarakat : Kolaborasi antara DEMA STIES dan Prodi Manajemen Bisnis Syariah di Desa Trayeman - M. Masrukhan; Nurul Wulandari Putri (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to describe the implementation of free acupuncture treatment as a form of community service carried out through collaboration between the Student Executive Board (DEMA) of the Islamic Economics College (STIES) and the Islamic Business Management Study Program in Trayeman Village. This free treatment is held to provide alternative health services to the underprivileged community, while introducing acupuncture as a non-medical treatment therapy that can help overcome various health complaints. The method used in this activity is direct treatment in the field by involving students and lecturers as medical personnel and companions. The results of the implementation of this treatment show an increase in public awareness of alternative medicine, as well as active community participation in the activity. The collaboration between DEMA STIES and the Islamic Business Management Study Program has also been proven to have a positive impact in terms of managing structured and well-coordinated community service activities. This activity is expected to be a model of community service that can be implemented more widely in various regions.